The impacts of Malaysian free trade agreements on margins of trade - Said, Rashidi; Ismail, Normaz Wana (Universiti Kebangsaan Malaysia, 2018)
The proliferation of Free Trade Agreements (FTAs) is a phenomenon in the world trading system. The number of FTA establishments has increased tremendously, from 55 in 1995 to more than 250 by end of 2014. Malaysia alone has signed twelve FTAs involving twenty trading partners. Using the most aggregated data at the Harmonized System six digit level from 1994 to 2014, this paper examines the impacts of twelve Malaysian FTAs on two trade adjustments: namely, extensive and intensive margins. Our results show that, for most of the FTAs, the trade is created along the intensive margin when FTAs enter into force. Interestingly, most of them are regional FTAs in which there has been a shift in overall trade patterns—a 4.0% reduction in trade of new products (extensive margin) generated from bilateral FTAs to a 41.6% increase in trade of existing products (intensive margin) from when regional FTAs entered into force. These findings may be contrary to the views that countries prefer to negotiate and sign more bilateral FTAs because of the trade benefits that may be gained from deeper market access than is possible with regional FTAs.